Hypoglycemia in type 1A diabetes can develop before insulin therapy: A retrospective cohort study. (January 2019) - Yamaguchi, Takeshi; Hachiya, Rumi; Watanabe-Yamamoto, Sayaka; Sawano, Kentaro; Morikawa, Shuntaro; Nakamura, Akie; Hasegawa, Yukihiro
Abstract: Aims: There are as yet no cohort studies of hypoglycemia in type 1 diabetes before starting insulin therapy. Our aim was to determine the frequency and clinical features of hypoglycemia in patients with type 1A diabetes prior to commencing insulin therapy. Methods: Eighty-seven patients with type 1A diabetes were enrolled, and a retrospective chart review of the patients was conducted. Results: Hypoglycemia before insulin therapy occurred in six of 87 patients (6.9%). The HbA1c levels at the diagnosis of type 1A diabetes in the hypoglycemia group were lower than in the non-hypoglycemia group (median: 7.3% (56 mmol/mol) vs. 11.9% (106 mmol/mol), p < 0.0001). Similarly, the 24-hour urinary C-peptide (UCPR) levels of the former group were higher than those of the latter group (16.5 μg/day/m 2 vs. 7.0 μg/day/m 2, p = 0.0075). Hypoglycemic episodes occurred mostly in the postprandial period and gradually disappeared with a decrease in insulin secretion. Conclusions: We demonstrated that some patients with type 1A diabetes experience hypoglycemic episodes before insulin therapy. Patients with early-stage type 1A diabetes with relatively low HbA1c or high UCPR have a risk of hypoglycemia. These findings may impact when and how insulin is introduced in the treatment of early-stage type 1A diabetes.